FROM NOVICE TO FLUENT - BELAID LOUIZA (Social Sciences and Education Research Review)
In this paper, we aim to investigate the incorporation of scaffolding strategies in the classroom, with a specific focus on stimulating and reinforcing the Zone of Proximal Development (ZPD). The main objective is to unveil the challenges that pupils face when learning a foreign language and to investigate the function of psycholinguistic techniques in improving the social and communication skills of young learners, enabling them to be self-regulated and autonomous. To collect data, a mixed-method design is employed, using both a questionnaire and a participant observation. The questionnaire evaluates the extent to which elementary school teachers of English in Tissemsilt, Algeria, use scaffolding in their classrooms. The participant observation aims to provide valuable insights into the functional use of these strategies in teaching English, specifically focusing on their impact on 3rd grade learners. The findings reveal that while the teachers exhibit their awareness of the scaffolding practical framework and its potential implications, the functional application of these strategies did not effectively target the learners' zone of proximal development. In this prospect, It is advisable to include psycholinguistic approaches in the training programs for teachers. This will promote their awareness of the scope and modernize the teaching strategies in foreign language learning.